Demystifying Conflict in Collaborative Writing: University EFL Students Case Study - Veniati Veniati; Endang Setyaningsih; Nur Arifah Drajati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The interaction between writers is essential in collaborative writing. Unfortunately, conflict could occasionally disrupt the interaction. This case study explores the conflict and negotiation among sixteen Indonesian graduate students during the collaborative writing. Three students were selected as focal respondents based on three criteria: (1) students’ engagement in learning, (2) students’ gender, and (3) English proficiency. The data of the study were mainly obtained from observations, interviews, and document analysis. The collected data were then analyzed using interactive model analysis. The study revealed three types of conflict in collaborative writing: (1) cognitive conflict, (2) socio-emotional conflict, and (3) process conflict. The conflict reasons, resolutions, and impacts were identified and discussed. This study implies that conflict during collaborative writing can impact students' writing quality.